ANALISA KETERTARIKAN MAHASISWA FAKULTAS EKONOMI DAN BISNIS PRODIK EKONOMI ISLAM ANGKATAN 2020 UNIVERSITAS JAMBI TERHADAP BELANJA PRODUK HALAL DI E-Commerce Shope ( Dalam perspektif Islam ) - Ary Dean Amri; Benny Zulfikar; Alfan Septiardo Ilham; Naufal Alfarizi HSB; Azzril Arya Hidayat; Raden Aqsal Safatullah; Mohan Tridipa Syamta (Yayasan Nusantara Hasana Berdikari, 2023)
This study aims to determine the interest of students of the Faculty of Economics and Business, Islamic Economics Study Program, Jambi University, University of Jambi, and have consumed or shopped for Halal products at e-commerce shopee. with 42 respondents as a sample from a total population of 115 Islamic economics students class of 2020 at the University of Jambi. The method used in this study was a qualitative descriptive method and data collection from this study was obtained from questionnaires. The data analysis technique in this study was to analyze the results of the questionnaires which were developed and described based on existing facts. So the results of the interest analysis study of students at the Faculty of Economics and Business, Islamic Economics Study Program, Jambi University, are positive because students are interested in shopping for Halal products at e-commerce shopee, with an average interest in online shopping according to Halal products in e-commerce shops, which are more dominant for women or Islamic economics student class of 2020 Jambi University compared to men or Islamic economics study program students class of 2020 Jambi University. This research is useful for all people in order to consume halal products at e-commerce shopee so that they are better than halal products.